Role of Nanoparticles in Enhancing Crop Tolerance to Abiotic Stress: A Comprehensive Review - El-Saadony, Mohamed T.; Saad, Ahmed M.; Soliman, Soliman M.; Salem, Heba M.; Desoky, El-Sayed M.; Babalghith, Ahmad O.; El-Tahan, Amira M.; Ibrahim, Omar M.; Ebrahim, Alia A. M.; Abd El-Mageed, Taia A.; Elrys, Ahmed S.; Elbadawi, Alaa A.; et al. (Frontiers in Plant Science, 2022)
Plants are subjected to a wide range of abiotic stresses, such as heat, cold, drought, salinity, flooding, and heavy metals. Generally, abiotic stresses have adverse impacts on plant growth and development which affects agricultural productivity, causing food security problems, and resulting in economic losses. To reduce the negative effects of environmental stress on crop plants, novel technologies, such as nanotechnology, have emerged. Implementing nanotechnology in modern agriculture can also help improve the efficiency of water usage, prevent plant diseases, ensure food security, reduce environmental pollution, and enhance sustainability. In this regard, nanoparticles (NPs) can help combat nutrient deficiencies, promote stress tolerance, and improve the yield and quality of crops. This can be achieved by stimulating the activity of certain enzymes, increasing the contents (e.g., chlorophyll) and efficiency of photosynthesis, and controlling plant pathogens. The use of nanoscale agrochemicals, including nanopesticides, nanoherbicides, and nanofertilizers, has recently acquired increasing interest as potential plant-enhancing technologies. This review acknowledges the positive impacts of NPs in sustainable agriculture, and highlights their adverse effects on the environment, health, and food chain. Here, the role and scope of NPs as a practical tool to enhance yield and mitigate the detrimental effects of abiotic stresses in crops are described. The future perspective of nanoparticles in agriculture has also been discussed.